2010
DOI: 10.1002/pmic.200900451
|View full text |Cite
|
Sign up to set email alerts
|

Other than IPG‐DALT: 2‐DE variants

Abstract: Special problems require special solutions. That is why, despite the trend towards standardization of the procedures in proteomic investigations, a number of alternative protocols, based on 2-DE, have been devised with time and are applied to the resolution of proteins on which the performance of IPG-DALT is poor. The difficult-to-handle samples include high pI, high molecular size and high hydrophobicity proteins. The protocol variants entail changes in the gel media and/or the use of unusual additives (often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 246 publications
(279 reference statements)
0
11
0
Order By: Relevance
“…Some review and/or practical papers are also of interest, either because they describe important caveats [36], or because they go deeper into more specialized topics, such as protein detection [37], non classical (i.e. without IEF) 2D gels [38] or variations to the basic electrophoretic protocols [39]. However, within the scope of this tutorial, we would like to show "the back side of the cards" in a stepwise fashion, and help the reader to understand the key parameters at play in 2D electrophoresis and the rationale underlying the protocols.…”
Section: Basic Conceptsmentioning
confidence: 99%
“…Some review and/or practical papers are also of interest, either because they describe important caveats [36], or because they go deeper into more specialized topics, such as protein detection [37], non classical (i.e. without IEF) 2D gels [38] or variations to the basic electrophoretic protocols [39]. However, within the scope of this tutorial, we would like to show "the back side of the cards" in a stepwise fashion, and help the reader to understand the key parameters at play in 2D electrophoresis and the rationale underlying the protocols.…”
Section: Basic Conceptsmentioning
confidence: 99%
“…In 2005, the first map‐based sequence of the annotated rice genome was also completed (International Rice Genome Sequencing Project, ). Entire genomes are now becoming available for some of the major crops, such as maize (Schnable et al, ), sorghum (Paterson et al, ), potato (Xu et al, ), tomato, soybean, domesticated apple (Velasco et al, ), or banana (D'Hont et al, ), as recently reviewed in (Feuillet et al, ; Miller, Eberinin, & Gianazza, ; Sonah et al, ) and at http://en.wikipedia.org/wiki/List_of_sequenced_eukaryotic_genomes. With the explosion in the amount of available data, it is increasingly difficult to provide a complete and updated picture of genome availability.…”
Section: Plant Proteomics and Mass Spectrometry: A Decadementioning
confidence: 99%
“…Classical 2-DGE is not suitable to analyze native proteins, protein complexes, and hydrophobic proteins. For an overview on the alternatives on classical 2-DGE, the reader is referred to Miller, Eberini, and Gianazza (2010). For a recent overview on the techniques used to analyze hydrophobic proteins in plants, readers are referred to Vertommen et al (2011b) and Kota and Goshe (2011).…”
Section: Protein Separationmentioning
confidence: 99%
“…In the present approach, we relied on 2DE under non‐reducing conditions as this allowed a better separation of the dominant protein IgG from proteinaceous impurities. As in other applications, this method has been able to visualize otherwise overlapping spot chains or patterns . In the present investigation, nonreducing 2DE proved useful for the study of protein impurities that differ between Ig products, as shown in Figs.…”
Section: Discussionmentioning
confidence: 65%